KOMPOSISI FUNCTIONAL SPECIES GROUP PADA SISTEM SILVIKULTUR TEBANG PILIH TANAM JALUR DI AREA IUPHHK-HA PT. SARPATIM, KALIMANTAN TENGAH Composition of Functional Species Group at Silviculture System of Tebang Pilih Tanam Jalur in IUPHHK-HA Area - Prijanto Pamoengkas; Ayi Kulsum Zamzam (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Forest management can have an impact on changes in forest structure and composition of plant species. Functional species Group (FSG) may explain the unity of the trees species that are selected in a group in a forest management activities so that it can help in explaining the characteristic of biodiversity such as the quality of habitat and ecosystem processes. The purpose of this research is to know the composition of forest vegetation that the production system are managed with a Silviculture system of TPTJ as seen from the forest structure and composition of the type that belongs to FSG for the stands and natural regeneration in log over area (LOA) and KPPN (The Conservation of Germplasm Area) IUPHHK-HA PT. Sarmiento Parakantja Timber (Sarpatim), Central Kalimantan. Analysis of the composition of the stands type and structure used terraced path in the area of TPTJ and KPPN. The results showed that the types of climax on an entire swath of observations, generally have greater proportion than the group of pioneers, the number of the climax type is 100 while pioneer type is 59. The structure of the stands form a J reverse curve, it show that the composition of vegetation recovery on log over areas managed by using TPTJ and KPPN Silviculture system has balance characteristic of uneven age forest. The value of diversity is high (H'>3). Most of tree and stands community have different communities (ID>50%).Key words: LOA, FSG, TPTJ, stand structure, composition of species